Recovery from AMPA Receptor Potentiation by Ampakines - Daniel P. Radin; Rok Cerne; Jodi L. Smith; Jeffrey M. Witkin; Arnold Lippa (Future Pharmacology)
Background: Ampakines are a family of molecules that enhance the functioning of AMPA-glutamate receptors (AMPAR). High-impact ampakines completely offset receptor desensitization and enhance agonist binding affinity, while low-impact ampakines only modestly affect receptor desensitization and do not alter agonist binding affinity. Nonetheless, little is known about AMPAR recovery following ampakine treatment. Methods: Herein, we study the effects of ampakines on AMPAR recovery and the interaction between high- and low-impact ampakines. Results: The high-impact ampakine CX729 did not induce any current in the absence of glutamate, but it dramatically increased glutamate-induced steady-state inward currents. Recoveries from the enhancement were significantly slower than those for the low-impact ampakine CX516, as was also seen on miniature synaptic currents. Electrophysiological interaction studies suggest that high- and low-impact ampakines may have different binding sites. We further investigated the induction of the potentiated response by measuring glutamate-induced responses after transient applications of CX729 or CX729 plus glutamate. Under both circumstances, subsequent application of glutamate yielded comparably potentiated responses. Furthermore, the recovery time was not different if saline was substituted for glutamate during the recovery period. Conclusions: These observations show that AMPAR potentiation by CX729 does not require the simultaneous presence of glutamate, nor is the slow reversal of the effects of the ampakine altered by subsequent receptor activation. Hence, the slow recovery from the effects of these select ampakines on the AMPAR may be the result of slow dissociation kinetics. We posit that the slow recovery of AMPAR from high-impact ampakines may contribute to the seizurogenic effects of this drug class and that high-impact ampakines that allow for more rapid AMPAR recovery may be safer and more clinically viable candidates.